Eletrodos modificados e não modificados na determinação de compostos sulfurados - um estudo comparativo - Vendrame, Zilda Baratto (2004)
The present study is a contribution for the electrochemical determination of the thiocompounds in aqueous solutions. The performance of different electrode surfaces as well as the introduction of modifiers in the electrolyte was evaluated. The electrodes used in this work were the hanging mercury drop electrode (HMDE), silver, gold, the amalgam-Ag/Hg and the carbon paste electrodes. Additionally, five different modifiers {o-phthalaldehyde (OPA), 5,5´-ditiobis(2-nitrobenzóic acid) (DTNB), copper (II) acetylacetonate [Cu(acac)2], nitroprussiato of sodium (NPNa) and copper (II) phthalocyanine tetraamines (FCTA)} were tested. The electrochemistry methods used were differential pulse voltammetry and cyclic voltammetry. Spectrophotometric measurements were also used to evaluate the interaction between analytes and modifiers. As sulfur containing compounds the thiotriazines, thiolcarbamates, cysteine, ethilenethiourea (ETU), ethanethiol and sulfide were investigated. The determination of thiotriazines was possible with Hg, Au, Ag/Hg and Ag/HgNPNa electrodes. The best voltammetric signals were obtained with the modified electrode Ag/HgNPNa. Among the investigated thiolcarbamates, dialate and molinate were assayed with the Ag/Hg electrode. Additionally, molinate was well detected by using the HMDE as the working electrode. Among the investigated electrodes to detect cysteine, Hg (HMDE) presented the best voltammetric signals. However, it was also verified that the electrode Ag/Hg provided the largest current peaks in the cysteine assay. Similarly, to detect ethanethi, the Ag/Hg electrode showed the best results when the modifier Cu(acac)2 was in the same solution as the analyte. For the determinations of ETU, the Ag/Hg electrode showed the highest sensitivity in the alkaline media. In this case the electrode Ag/Hg is a simple alternative for the direct detection of the species in solution. Despite the high voltammetric signal obtained for sulfide ions by using the Ag electrode, the resolution was not good. Comparatively good peaks for sulfide were obtained by using Hg and Ag/Hg with Cu(acac)2 as modifiers.